Studi Kekuatan Sambungan Batang Tarik Pelat Baja Dengan Alat Sambung Baut - Mery Silviana (LPPM Politeknik Aceh Selatan, 2017)
Steel as one of construction materials has several advantages compared to other construction materials. One of the advantages is it can withstand large tensile loads compared to wood and concrete. This research was conducted to find out the strength of the connection of two-faced steel plate tension member with bolts connection through experiment and compare it with theoretical calculations by using Allowable Stress Design (ASD) method. The focused structure is a two-faced connection tension member that is connected using bolts. Steel plated that used in this research are 8 mm and 10 mm thickness with bolt sizes Ø ¼